Competition and Market Integration – Role of European Power Exchanges - Mrhač, Václav; Němcová, Ingeborg, 1957-; Jegers, Marc; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The main focus of this thesis is to find out degree of market integration in power exchanges in the European Union. Well integrated electricity markets imply existence of single European electricity market and advanced level of liberalization process in this sector. The thesis provides estimates of degree of market integration for six most evolved European power exchanges. Therefore, British, Dutch, French, German, Spanish and Scandinavian power exchanges have been selected during sample period 2004 - 2012. After conducting correlation and convergence analysis, the results have not suggested existence of single European electricity market and prove the effect of liberalization at regional level.
Vedoucí práce: Ingeborg Němcová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]